1999
DOI: 10.1016/s0167-8116(98)00026-3
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous model for innovative product categorysales diffusion and competitive dynamics

Abstract: Diffusion of innovation has been the focus of an entire stream of research in marketing, and firm entry and exit decisions have been investigated by marketers, strategists, and economists. However, little attention has been paid to the relationship between changing demand and the entry and exit behaviors of competitors in the marketplace. Understanding this relationship is essential in making resource commitments, as profitability of options depends not only on the size and growth of the market, but also on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Those firms who are not as competitive as their rivals eventually go out of business or exit markets. In an empirical study, Kim, Bridges, and Srivastava (1999) confirmed that competition impact entry and exit. For example, The Bank of Yokohama, a Japanese bank, announced that it plans to retreat from international operations mainly because of competition from the recent Deutsche Bank -Bankers Trust merger (Rowley, 1999).…”
Section: Competitionmentioning
confidence: 78%
“…Those firms who are not as competitive as their rivals eventually go out of business or exit markets. In an empirical study, Kim, Bridges, and Srivastava (1999) confirmed that competition impact entry and exit. For example, The Bank of Yokohama, a Japanese bank, announced that it plans to retreat from international operations mainly because of competition from the recent Deutsche Bank -Bankers Trust merger (Rowley, 1999).…”
Section: Competitionmentioning
confidence: 78%
“…SUR accounts for correlations across the error terms of the two equations which typically leads to lower standard errors and therefore more efficient estimators (Kim et al, 1999;Pindyck and Rubinfeld, 1991). The same estimation strategy was used by Kim et al (1999) in a similar context (diffusion of innovations).…”
Section: Estimation Resultsmentioning
confidence: 99%
“…SUR accounts for correlations across the error terms of the two equations which typically leads to lower standard errors and therefore more efficient estimators (Kim et al, 1999;Pindyck and Rubinfeld, 1991). The same estimation strategy was used by Kim et al (1999) in a similar context (diffusion of innovations). In addition to a full model incorporating both information variables, we also estimated two other benchmark models: A "null' model with no information variables and a "pooled information" model where technology and availability information were pooled in one variable using the share-of-voice measure.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…The exit of such foreigners from the hotel industry can be observed as a corrective mechanism, provided the high possibility of being beaten by larger and global competitors (Fornell & Wernerfelt, 1987). It has been seen that the competition of foreigner bodies with bigger rivals, including the international ones, can majorly affect stature in market; thus, influencing their exit and entry from and into the industry (Kim, Bridges & Srivastava, 1999). Departure of foreigners can also be interpreted as an attempt to avoid harnessing of resources in investment for change (Karakaya, 2000).…”
Section: Discussionmentioning
confidence: 99%